Experimental Characterization of the Influence of Lateral Pass Width on Results of a Ball Burnishing Operation. (2015) - Gomez-Gras, G.; Travieso-Rodriguez, J.A.; Jerez-Mesa, R.
Abstract: Ball burnishing has proved to be a highly effective mechanical finishing process of industrial workpieces, because of the excellent surface roughness and fatigue performance that induces in treated workpieces. In order to obtain specific target results from this complex plastic deformation process, its parameters must be accurately controlled. This paper focuses on the influence of the lateral pass width on the average surface roughness of aluminum 2007. Two values of lateral pass width are tested, with two control variables: number of burnishing passes and applied burnishing force. Furthermore, the ball burnishing operation is performed with two different tools: a conventional non-assisted ball-burnishing tool, and a vibrations-assisted one. The most suitable lateral pass width proves to be the distance between the highest peak and lowest vale of the P-profile of the burnishing path, and significantly better results are obtained by assisting the process with vibrations. At the end of the paper, values for lateral pass width for each group of operation conditions are recommended.